Impact of spectators, league and team ability on home advantage in professional European basketball - Pérez-Chao, E. A.; Portes, R.; Ribas, C.; Lorenzo, A.; Leicht, A. S.; Gómez, M. Á. (Perceptual and Motor Skills, 2024)
Our aim in this study was to examine the impact of fans (vs. no fans), geographical location of league, and team ability on home winning percentage (HW%) or home advantage (HA) in professional European basketball. Data were collected from five prestigious professional, national basketball leagues within Europe (Spain, Germany, Italy, Greece and Israel) across 16 regular seasons (2005-2006 to 2020-2021). We conducted comparisons between matches with and without fans, location of leagues, team ability (High, Medium, Low), and combinations of these factors via non-parametric tests (e.g., Mann-Whitney tests, Kruskal-Wallis). We found significantly greater HA during matches with fans for leagues in Germany (p = .001), Italy (p = .012) and Spain (p = .002). For matches with fans, HA and HW% were significantly different between several, but not all, leagues for high (p < .05), medium (p < .05) and low (p < .02) team abilities. In conclusion, HA and HW% were enhanced by spectator attendance, with this phenomenon varying by location/region and team ability. Consideration of these multiple contextual factors may assist coaches and sport organizations to develop key strategies for enhanced team success.